he Level of Public Knowledge About Multivitamins And Medicine Used Towards Dagusibu Socialization To Expectants Mothers And Mothers Who Have Children In Dasan Tapen Village, Gerung District, West Lombok - Putri Amalia; Husnul Khuluq; Rafila Intiyani (Prosiding University Research Colloquium, 2022)
The knowledge about the usage of drugs must be owned by all people. The negative impact is the lack of public knowledge about drug management procedures such as using and disposing of drug waste. Public service is carried out by socializing DAGUSIBU to the village, especially mothers who have toddlers and expectant mothers. Respondents from this socialization were given material about DAGUSIBU directly using pocketbook media. Socialization activities were carried out by giving pretest, the delivery of material, giving pocketbooks, and giving posttest. The results of the pretest in the good category were 9 respondents, the medium category was 30 respondents, and the low category was 21 respondents. The posttest results in the good category were 39 respondents, the medium category was 21 respondents, and the low category was 0 respondents.The results of the provision of these materials indicate a relationship that after socialization, public knowledge has increased